2020
DOI: 10.1021/acs.jpcc.9b11942
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Propylene Dehydrogenation and Linear Atomic Chain Formation on Ni(111)

Abstract: The structures formed by propylene adsorption on Ni(111) at room temperature are determined by a combination of scanning tunneling microscopy and density functional theory. As a result of the interaction with the Ni(111) surface, propylene molecules are dehydrogenated and coupled into linear hydrocarbon chains. The length of the chains varies from 8 to 60Å, with the most frequently observed length of 18Å. At saturated coverage, some chains are closed in rings with a diameter of 6Å. The chains C12H12 (four C3H3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…To fully understand the nature of the new confined features observed in the STM images of nanopores, we have carefully surveyed the literature. We found that very similar types of confined features have been recently observed after exposure to 300 L of propylene on a clean Ni(111) surface at room temperature . The authors corroborated their experimental observations by DFT simulations.…”
Section: Discussion and Dft Simulationssupporting
confidence: 87%
See 2 more Smart Citations
“…To fully understand the nature of the new confined features observed in the STM images of nanopores, we have carefully surveyed the literature. We found that very similar types of confined features have been recently observed after exposure to 300 L of propylene on a clean Ni(111) surface at room temperature . The authors corroborated their experimental observations by DFT simulations.…”
Section: Discussion and Dft Simulationssupporting
confidence: 87%
“…The TCNBB molecule exhibits six bright protrusions (white dashed circles in Figure 2d), and each protrusion included in nanopores is attributed to a silicon adatom. This model is also similar to the one observed for the bromine-ended molecule 34 instead of cyano-ended.…”
Section: Moleculessupporting
confidence: 86%
See 1 more Smart Citation
“…[13,[19][20][21] Small hydrocarbon molecules were directly dosed on model catalyst surfaces, [22,23] forming polymeric chains. [24][25][26] A recent in situ STM study clarified the growth process of polyethylene on a carburized Fe(110) surface, unraveling the ethylene insertion mechanisms proposed by Cossee for Ziegler-Natta catalysts. [3] In this case, the active sites were identified as the boundaries between the iron carbide domains.…”
Section: Introductionmentioning
confidence: 97%
“…In an attempt to investigate the C−C bond formation step, ultra‐high vacuum (UHV) studies have been reported [13, 19–21] . Small hydrocarbon molecules were directly dosed on model catalyst surfaces, [22, 23] forming polymeric chains [24–26] . A recent in situ STM study clarified the growth process of polyethylene on a carburized Fe(110) surface, unraveling the ethylene insertion mechanisms proposed by Cossee for Ziegler–Natta catalysts [3] .…”
Section: Introductionmentioning
confidence: 99%